Direct spray pyrolysis of aluminum chloride solution for alumina preparation - Lü, Guo-zhi; Zhang, Ting-an; Wang, Long; Ma, Si-da; Dou, Zhi-he; Liu, Yan (Journal of Central South University, 2014)
The effects of pyrolysis mode and pyrolysis parameters on Cl content in alumina were investigated, and the alumina products were characterized by XRD, SEM and ASAP. The experimental results indicate that the spray pyrolysis efficiency is higher than that of static pyrolysis process, and the reaction and evaporation process lead to a multi-plot state of the alumina products by spray pyrolysis. Aluminum phase starts to transform into γ -Al 2 O 3 at spray pyrolysis temperature of 600 °C, which is about 200 °C lower than that of static pyrolysis process. The primary particle size of γ -Al 2 O 3 product is 27.62 nm, and Cl content in alumina products is 0.38% at 800 °C for 20 min.